Force overestimation during vascular occlusion is triggered by motor system inhibition - Yudai Takarada; Daichi Nozaki (Scientific Reports)
Abstract Low-intensity resistance exercise with vascular occlusion enhances human muscular strength by elevating neural drive to muscles, which is accompanied by the additional activation of fast-twitch fibers because of muscle fatigue. However, few previous studies have investigated the underlying neuromotor mechanisms from a perspective other than muscle fatigue. Notably, participants require more voluntary effort to exert muscular force to lift a weight immediately after vascular occlusion, indicating its acute effect on the force perception system without muscle fatigue. However, the major cause of force overestimation under these conditions remains unclear. We sought to elucidate the neural mechanism of force exertion combined with tourniquet-induced vascular occlusion, with special reference to exerted force perception, using motor evoked potentials in response to transcranial magnetic stimulation applied over the contralateral primary motor cortex as well as upper extremity H-reflex measurements. Rapid force overestimation was accompanied by the instantaneous inhibition of spinal motoneuron and corticospinal tract excitability. Thus, force overestimation may be caused by motor-related cortical areas functioning as the source of excitatory input to the corticospinal tract; participants would be unable to exert the same handgrip force as with normal blood flow without a compensatory input to the corticospinal tract from motor-related cortical areas.